Mammadova, Leyla - (:unkn) unknown (My University, 2026)
Leyla Vasif qizi Mammadova graduated from Rostov State University in the Russian Federation in 1999 with a degree in Soil Science and Agrochemistry. She subsequently obtained a Master’s degree in Geographical Ecology from Baku State University in 2004. She began her professional career in 1993 at the Ecological and Educational Center of the Nakhchivan Republic and later worked at the State Land Cadastre and Monitoring Science-Production Center, where she held engineering positions in property registration and land records. From 2012 to 2015, she worked as a Lecturer at the Department of Land Management and Cadastre at Baku State University. She also participated in the EU Twinning Project aimed at developing a modern state land cadastre registration system in Azerbaijan. From 2021 to 2023, she worked as a Senior Agricultural Technician (Lecturer-Instructor) at the Research Institute of Crop Husbandry of the Ministry of Agriculture of Azerbaijan. She also served as a Senior Lecturer at the Department of Engineering Geodesy, now the Department of Geomatics, at the Azerbaijan University of Architecture and Construction (AzUAC). Since December 2025, she has continued her academic activities at the same department as an Assistant Lecturer. Leyla Mammadova has also worked as a foreign expert for the Independent Agency for Accreditation and Rating (IAAR) and is the author of 16 scientific articles.